Psychodrama : a beginnerʹs guide - Đurić, Zoran, 1954- (Jessica Kingsley Publishers, 2006)
This is a clear, delightful and excellent book about psychodrama that will be useful to experienced psychodramatists, trainees, family and group therapists and also to laypeople interested in psychodrama.''. - Anne Schutzenberger, U.N. Psychodrama expert. Psychodrama is a unique and entertaining beginner's guide to this active form of group psychotherapy, in which individual life situations, fears, inhibitions and emotions are explored on stage in a safe, non-judgemental and stimulating environment. The authors, professional psychodramatists Zoran Djuric and Jasna Veljkovic, explain in user-fr.